Genus β human papillomaviruses and incidence of basal cell and squamous cell carcinomas of skin: population based case-control study. (8th July 2010) - Karagas, Margaret R; Waterboer, Tim; Li, Zhongze; Nelson, Heather H; Michael, Kristina M; Bavinck, Jan Nico Bouwes; Perry, Ann E; Spencer, Steven K; Daling, Janet; Green, Adele C; Pawlita, Michael
Abstract : Objective To investigate the association between genus β human papillomaviruses and the incidence of non-melanocytic skin cancer in the general population. Design Population based case-control study. Setting New Hampshire, USA. Participants 2366 skin cancer cases and controls from the general population aged 25 to 74 years (663 squamous cell carcinoma, 898 basal cell carcinoma, 805 controls), with plasma samples tested for L1 antibodies to 16 genus β human papillomaviruses by multiplex serology. Main outcome measures Odds ratios for squamous cell carcinoma and basal cell carcinoma associated with seropositivity to β human papillomaviruses. Results Squamous cell carcinoma, but not basal cell carcinoma, cases had a higher prevalence of each of the individual β human papillomaviruses assayed compared with controls. The odds ratios for squamous cell carcinoma increased with the number of β types positive (odds ratio for one type positive 0.99 (95% confidence interval 0.74 to 1.33); two to three types positive 1.44 (1.03 to 2.01); four to eight types positive 1.51 (1.03 to 2.20); more than eight types positive 1.71 (1.12 to 2.62); P for trend (categorical)<0.001; P for trend (continuous)=0.003). With limited statistical power, the association was stronger among long term users of systemic glucocorticoids (odds ratio 3.21, 1.22 to 8.44) than among non-users (1.23, 0.97 to 1.55). Conclusions These findings support a relation between genus β human papillomavirus infection and the incidence of squamous cell carcinoma of the skin in the general population, as well as potential enhancement of risk by immunosuppression.